Intelligent swarm-based optimization technique for oscillatory stability assessment in power system - N. A. M. Kamari; I. Musirin; A. A. Ibrahim; S. A. Halim (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
This paper discussed the prediction of oscillatory stability condition of the power system using a particle swarm optimization (PSO) technique. Indicators namely synchronizing (Ks) and damping (Kd) torque coefficients is appointed to justify the angle stability condition in a multi-machine system. PSO is proposed and implemented to accelerate the determination of angle stability. The proposed algorithm has been confirmed to be more accurate with lower computation time compared with evolutionary programming (EP) technique. This result also supported with other indicators such as eigenvalues determination, damping ratio and least squares method. As a result, proposed technique is achievable to determine the oscillatory stability problems.